1997
DOI: 10.1002/j.1550-8528.1997.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Islet Size and Islet Size Distribution Resulting from Protein‐Malnutrition in Lean (Fa/Fa) and Obese (fa/fa) Zucker Rats

Abstract: Potential alterations in islet size and islet size distribution resulting from protein malnutrition were studied in lean ( F d F u ) and obese (fuNu) Zucker rats. The purpose was to investigate whether the distribution of enlarged islets in obese rats was altered by low-protein feeding. Four-week-old, male, lean and obese Zucker rats were fed either a diet containing 20% (w/w) protein (control diet) or a diet containing 5% (w/w) protein (low-protein diet) for 3 weeks. Pancreata were dissected at autopsy and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
3
11
0
1
Order By: Relevance
“…Our data also confirm previous studies (8,9) showing that rats submitted to a low-protein diet exhibit reduced β-cell mass ( Figure 1C). An increase in the population of small islets and a decrease in the population of large islets were observed by Tse et al (9), as also observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data also confirm previous studies (8,9) showing that rats submitted to a low-protein diet exhibit reduced β-cell mass ( Figure 1C). An increase in the population of small islets and a decrease in the population of large islets were observed by Tse et al (9), as also observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…An increase in the population of small islets and a decrease in the population of large islets were observed by Tse et al (9), as also observed in the present study. Smaller islets can be easily observed in pancreas sections from LP rats ( Figure 1B), which were in agreement with the reduced mean islet size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…6 There are also reports in other rat strains (Zucker lean and obese), that large islets are specifically decreased in animals subjected to protein malnutrition. 49 A recent study also showed decreased area of large islets in offspring of Wistar rats fed a low-protein diet. 50 Whether or not very large islets seen in BBc rats are a common feature of islet size distribution in humans remains unclear.…”
Section: Discussionmentioning
confidence: 94%